Oxidative metabolism and physiological quality of artifi cially agedArachis hypogaea L. seeds - de Lima, Leandro Dias; Pereira Gonçalves, Edilma; Moreira, Keila Aparecida; Marques Rodrigues, Caroline; Ralph, Lidiana Nayara; Silva Viana, Jeandson; Alves Diniz da Silva, Monalisa (Revista Ciência Agronômica, 2021)
Peanut (Arachis hypogaea L.) is an oleaginous plant that is well-adapted to the climatic conditions in the northeast ofBrazil. However, there is little information on the existing cultivars in the region with regards to their behavior under stress conditionsand the biochemical changes of the seeds. The objective of this study was to investigate the physiological and biochemical changes inaged peanut seeds. The experiments were conducted at the Seed Analysis Laboratories (LAS) and Biotechnology of CENLAG, FederalUniversity of Agreste of Pernambuco (UFAPE). Seeds of two cultivars, IAC Tatu ST and Caiana, were artifi cially aged at 42 °Cand 100% relative humidity for 96 h, and removed every 24 h for evaluation. Physiological potential was evaluated using germination,vigor test, and enzymatic modifi cations as the parameters. An increase in the accelerated aging period resulted in physiological andbiochemical changes in the seeds of both cultivars. The activity of the enzymes in the aged peanut seeds was specifi c to the cultivarused, and the seeds of the cultivar Caiana had less vigor and decreased activity of the enzyme catalase.